Low-alkalinity casting powder for peritectic alloy steel and preparation method of low-alkalinity casting powder
By adopting low-alkaline protective slag and using components such as MnO2, ZrO2 and F, the problems of microcracks and slag rings during continuous casting of crystalline alloy steel are solved, and the surface quality of the casting billet is significantly improved.
Patent Information
- Application Number
- CN202411839934.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
AI Technical Summary
During continuous casting, crystal-clad alloy steel is prone to surface quality defects in the casting billet, especially microcracks and slag ring problems, which affect the overall quality of the casting billet.
Using low-alkaline protective slag, by selecting the appropriate raw material composition and process flow, a protective slag with an alkalinity of 0.55-0.85, a melting point of 1190-1260℃ and a viscosity of 0.28-0.79Pa·s was prepared. The protective slag contains components such as MnO2, ZrO2 and F, which can promote crystallization and nucleation, improve the thermal resistance of solid slag film, reduce the heat flux in the crystallizer, and thus reduce the occurrence of microcracks and slag circles.
It effectively improves the continuous casting quality of crystalline alloy steel, reduces the chance of microcracks, reduces or avoids slag ring problems, and improves the surface quality of the casting billet.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of steelmaking metallurgical auxiliary materials, and in particular relates to a low-basicity protective slag for peritectic alloy steel and a preparation method thereof. Background Art
[0002] As a steel with special properties, peritectic alloy steel has high strength, high toughness and good impact resistance and is widely used in many fields such as machinery manufacturing, automobile manufacturing, aerospace, shipbuilding, bridge construction, mining machinery, etc. With the continuous advancement of science and technology and the continuous development of industrial production, the application field of peritectic alloy steel will continue to expand and deepen. Peritectic alloy steel has a wide range of uses and a large amount of use. According to preliminary statistics, the annual output can reach 80 million tons. At present, the production process is mainly based on blast furnace-converter-refining-continuous casting-rolling and electric furnace-refining-continuous casting-rolling.
[0003] Molten steel with a carbon content of about 0.08% to 0.15% will undergo peritectic reaction during solidification, which is accompanied by large volume changes and linear shrinkage. During continuous casting, it is easy to cause mold leakage accidents and surface quality defects of the ingot. It is one of the more difficult steels to cast, and this type of steel is usually called peritectic steel. Peritectic alloy steel usually contains a large amount of alloying elements, such as Mn, Si, Ni, V, Ti, Cr, Nb, etc. The main function of these alloying elements is to strengthen the performance of the steel.
[0004] The main problem of the surface quality of the ingot in the continuous casting production process of peritectic alloy steel is the crack problem. At present, the continuous casting protection slag of this type of steel mainly controls heat transfer by increasing the basicity. Relevant studies have shown that with the increase of the basicity of the protection slag, the glass transition characteristics of the protection slag weaken, and the crystallization rate increases. When the basicity is greater than 1.1, crystals begin to precipitate in the protection slag. When the basicity reaches 1.15~1.20, the crystallization rate of the protection slag reaches 30%~60%, and when the basicity reaches 1.3, the crystallization rate of the protection slag reaches 100%. Therefore, the basicity of the protection slag of peritectic steel is conventionally controlled to be above 1.3, basically between 1.30-1.90. However, due to its high basicity and strong sintering characteristics, this type of protection slag is prone to produce slag rings, extruding the billet shell to cause defects in the casting, and even rolling slag and leaking steel, which also affects the operation of workers. In addition, since this type of protection slag mainly relies on Na2O and F to control the melting point and viscosity, this type of substance enters the secondary cooling water, which will cause water pollution in the secondary cooling water. Therefore, it is necessary to propose a solution to effectively improve the surface quality defects of peritectic alloy steel ingots. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a peritectic alloy steel continuous casting protection slag to improve the casting quality of the peritectic alloy steel and reduce the probability of microcracks.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: A low-basicity protective slag for peritectic alloy steel is made from the following raw materials in parts by weight: 5-8 parts of fluorite, 0-5 parts of wollastonite, 0-3 parts of soda ash, 31-39 parts of manganese slag, 1-11 parts of limestone, 4.5-14 parts of glass powder, 2-5.5 parts of calcined aluminum ash, 4-8 parts of magnesium powder, 10-16 parts of manganese dioxide powder, 3-8 parts of zirconium oxide powder, 6-11 parts of carbonaceous material and 2-3 parts of binder.
[0007] Optionally, the manganese slag is the molten waste slag at the bottom of the furnace after smelting metallic manganese, and its chemical composition is calculated by mass percentage as follows: SiO2: 37.0-43.0%, CaO: 20-26.0%, Al2O3: 10.0-16.0%, Fe2O3: 1.0-2.0%, MgO: 4.0-7.0%, MnO2: 8.5-12%, and the rest are impurities.
[0008] Optionally, the carbonaceous material is a composition of earthy graphite, medium carbon graphite and carbon black, and the mass ratio of the earthy graphite, medium carbon graphite and carbon black is (2-4): (2-4): (2-3).
[0009] Optionally, the binder is sodium carboxymethyl cellulose or dextrin.
[0010] Optionally, the low-basicity protective slag for peritectic alloy steel has the following chemical compositions in percentage by mass: SiO2: 18.5-25.5%, CaO: 12.3-22.0%, MgO: 5.5-10.0%, Fe2O3: 0.4-0.5%, Al2O3: 6.0-10.2%, Na2O: 0.75-4.0%, F: 2.3-4.0%, ZrO2: 2.5-8.5%, MnO2: 10.0-15.5%, C: 5.0-10.5%, and the remainder is the loss-on-burning component.
[0011] Optionally, the basicity of the protective slag is 0.55-0.85, the melting point of the protective slag is 1190-1260° C., and the viscosity of the protective slag is 0.28-0.79 Pa·s.
[0012] The present invention also provides a method for preparing the above-mentioned low-basicity protective slag for peritectic alloy steel, comprising the following steps: (1) Stir the manganese slag evenly, dry it to make its moisture content ≤1%, and crush it to a particle size of less than 300 mesh and ≥97%; (2) Weighing each raw material by weight, placing it in a pulping tank, adding water and stirring, controlling the slurry concentration to 0.65-0.70%, and preparing a mixed slurry; conveying the mixed slurry to a water mill for grinding, and pumping the ground slurry to the pulping tank during grinding for cyclic grinding; (3) The slurry after circulating grinding is placed in a low-level tank and pressurized into a spray drying tower for spray granulation; (4) Screening out particles with a particle size of 20-80 mesh to obtain the product; (5) Sampling and testing of chemical composition; (6) Packaging and storage.
[0013] Furthermore, in the step (2), the stirring time is 10-20 minutes, and the circulating grinding time is 40-60 minutes.
[0014] Furthermore, in the step (3), the slurry is pressurized to 1.2-1.8 MPa, the aperture of the spray plate is 2.5 mm, the temperature inside the spray drying tower is 450-600° C., the outlet temperature is 150-180° C., and the moisture content of the product is controlled at 0.1-0.35%.
[0015] During the continuous casting process, the casting of peritectic alloy steel is very easy to produce micro cracks at the corners, also known as star cracks or transverse cracks at the corners. The carbon content in peritectic alloy steel is generally 0.08-0.14%. According to the iron-carbon phase diagram, this type of steel undergoes a structural change of L→L+δ→δ+γ→γ as the temperature decreases during solidification. The density of δ ferrite is 0.5-1.0% lower than that of γ austenite, and there is a large volume shrinkage during solidification. Therefore, during the continuous casting production process, the shrinkage and extrusion of the billet shell leads to stress concentration. Once the billet shell is uneven, the stress will be released and cracks will be generated.
[0016] Furthermore, peritectic alloy steel also contains a large amount of alloying elements for strengthening performance, such as Mn, Si, Ni, V, Ti, Cr, Nb, etc. Such alloying elements are also easy to increase intergranular stress while strengthening steel performance. If the uneven heat transfer of the shell leads to uneven thickness of the shell, intergranular fracture will occur, and microcracks will occur during the extension fracture process. And the V, Ti, Nb in the peritectic alloy steel have a strong binding force with carbon and nitrogen elements, and the recrystallization of austenite is regulated by forming stable high melting point carbonitrides, grain refinement, and precipitation strengthening effect is produced on the matrix during the phase change process, so as to achieve the purpose of improving the strength and toughness of steel. However, in the case of poor control, these alloy precipitates are precipitated at the austenite grain boundaries, which will aggravate the sensitivity of grain boundary cracks, easily induce cracks, and further aggravate the crack problem in the continuous casting process.
[0017] In the actual continuous casting production process, in addition to the microcrack defects, peritectic alloy steel will also have other defects due to the improper use of continuous casting process and its protective slag, such as slag ring. Peritectic alloy steel usually needs to be deoxidized with single element aluminum during continuous casting. To ensure the deoxidation effect, acid-soluble aluminum residue is generally required in the molten steel. However, as the casting process proceeds, single element aluminum easily reacts with silicon dioxide in the liquid slag to form aluminum oxide, consumes silicon dioxide, and causes the basicity of the protective slag to increase; at the same time, aluminum oxide enters the slag system, which will cause the viscosity and melting point of the slag to increase, and then lead to poor introduction and insufficient flow of protective slag. As the viscosity increases, the slag film thickens, heat transfer is hindered, and it adheres to the wall of the crystallizer, making it easier to produce slag rings; the higher the melting point, the easier it is to form various slag rings during the temperature drop process, which ultimately leads to an increase in slag ring defects. The above is a process of slow slag denaturation, accompanied by the generation of slag rings.
[0018] Therefore, it is easier to obtain good continuous casting billet surface quality by selecting and using protective slag that matches the characteristics of peritectic alloy steel. Otherwise, it is easy to produce defects such as batch surface cracks and slag rings, resulting in reduced billet quality. However, the selection of protective slag for peritectic alloy steel is complex, and it is necessary to comprehensively consider factors such as heat flow control, crystallization characteristics, lubrication properties, and physical properties during the continuous casting of peritectic alloy steel. Therefore, the design ideas of protective slag for continuous casting of peritectic alloy steel in the prior art vary greatly, such as material composition and parameters such as basicity, melting point, viscosity, and crystallization temperature, each of which has its own characteristics, and there is no fixed design pattern to ensure the stability of the continuous casting process and the quality of the billet.
[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention designs a protective slag with low basicity, relatively low viscosity and high melting point according to the steel grade characteristics of peritectic alloy steel. Under the action of the protective slag, the continuous casting quality of peritectic alloy steel can be improved, the probability of microcracks can be reduced, and the slag ring problem can be reduced or avoided.
[0020] First, the influence of the basicity of the protective slag on the characteristics of the protective slag is relatively complex. The basicity (CaO / SiO2) of the protective slag designed by the present invention is 0.55-0.85. For this reason, the present invention selects a high content of 10.0-15.5% of the component MnO2 to reduce infrared thermal radiation heat transfer, increase the thermal resistance of the solid slag film, and slow down heat transfer; at the same time, 2.5-8.5% of the component ZrO2 is added to promote crystallization nucleation, increase the crystallization rate, and further control heat transfer; and a certain proportion of fluoride (2.3-4.0% F) is added to promote the precipitation of lanceolite crystals. After the crystals are precipitated, the thermal conductivity of the slag film is further reduced. Through the synergistic combination of the above-mentioned components, the purposes of promoting the crystallization of the slag film, increasing the crystallization rate, increasing the thermal resistance of the solid slag film, and reducing the heat flux in the crystallizer are achieved at low basicity, so that the shell shrinks slowly and the generation of microcracks is reduced or avoided.
[0021] Second, based on the continuous casting deoxidation requirements of peritectic alloy steel, low-basicity protection slag can also alleviate the level and speed of basicity increase during the long casting process (continuous casting of more than 12 furnaces), enhance heat transfer to a certain extent, reduce or offset the negative impact of the reaction of the deoxidizer elemental aluminum, prevent slag denaturation, improve the sintering characteristics of the protection slag during the melting process, avoid the formation of slag rings, and effectively solve the problem of traditional protection slag prone to slag rings during the long casting process of peritectic alloy steel.
[0022] Third, the melting point of the protective slag of the present invention is 1190-1260°C, and the viscosity is 0.28-0.79Pa·s. The present invention uses MnO2 as the main flux and Na2O and F as auxiliary fluxes to effectively reduce the melting point and viscosity of the slag and obtain a suitable range of protective slag performance; at the same time, MnO2 replaces most of the Na2O and a small part of the fluoride, reducing the pollution problem of Na2O and F to the circulating water system. And the surface tension coefficient of MnO2 is higher than that of Na2O and F, which is beneficial to increase the surface tension of the slag, making it easy to separate steel and slag and reducing the probability of slag rolling. In addition, adding an appropriate amount of MnO2 can slow down the Mn oxidation reaction in the positive reaction direction, effectively reduce the amount of Mn element oxidation products in the steel entering the slag, and reduce the degree of slag denaturation.
[0023] Fourth, the raw material of the present invention adopts the molten waste slag from the furnace bottom after the smelting of metallic manganese (referred to as manganese slag). As a high-quality melting material, manganese slag has been proved by the present invention to be completely able to replace the protective slag pre-melting material, and the output of this type of waste slag is very large and the price is very low. The waste slag also contains 8.5-12.0% MnO2. The use of this type of waste slag can not only improve the product quality, but also partially replace the amount of Mn-containing materials, which can greatly reduce the cost and has good economic benefits. At the same time, the present invention provides a new and high-added method for the digestion of such solid waste, which has good social and environmental benefits. When manganese slag is used as raw material to produce low-basicity peritectic alloy steel protective slag, it is necessary to first detect the chemical composition of the manganese slag. The chemical composition of the manganese slag that can be used as raw material is: SiO2: 37.0-43.0%, CaO: 20-26.0%, Al2O3: 10.0-16.0%, Fe2O3: 1.0-2.0%, MgO: 4.0-7.0%, MnO2: 8.5-12%, and the rest are impurities. Only after the composition meets the requirements can subsequent processing be carried out and then used according to the formula requirements of low-basicity peritectic alloy steel protective slag.
[0024] Fifth, the present invention uses glass powder and calcined aluminum ash as raw materials for the production of protective slag. While enhancing the performance of the protective slag, it reduces the use of natural mineral raw materials, achieves resource protection, and has good ecological benefits. In addition, it also provides a new, high-added-value method for the use of such recycled materials, which has good social benefits. At the same time, the price of such recycled materials is lower than that of genuine raw materials, which can effectively reduce the cost of protective slag, improve product competitiveness, and has good economic benefits.
[0025] Sixth, the protective slag of the present invention adopts a combination of cyclic grinding and spray drying technology, so that the material is fully ground and mixed, the utilization rate is high, the composition of the protective slag particles is uniform, and it is not easy to segregate, the quality and stability of the protective slag product are improved, the particle size and morphology of the product are uniform, the spreadability and fluidity of the product are enhanced, the performance of the protective slag in the continuous casting of peritectic alloy steel is improved, and the occurrence of defects such as microcracks and slag rings is reduced. DETAILED DESCRIPTION
[0026] In order to better understand the present invention, the content of the present invention is further clearly set forth in conjunction with the embodiments below, but the protection content of the present invention is not limited to the following embodiments. In the following description, a large number of specific details are provided in order to provide a more thorough understanding of the present invention. However, it is obvious to those skilled in the art that the present invention can be implemented without one or more of these details.
[0027] In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not as limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0028] Unless otherwise specified, all raw materials are from commercially available products and do not contain other unspecified components except inevitable impurities unless otherwise specified.
[0029] In some specific embodiments, a low-basicity protective slag for peritectic alloy steel has the following chemical compositions by mass percentage: SiO2: 18.5-25.5%, CaO: 12.3-22.0%, MgO: 5.5-10.0%, Fe2O3: 0.4-0.5%, Al2O3: 6.0-10.2%, Na2O: 0.75-4.0%, F: 2.3-4.0%, ZrO2: 2.5-8.5%, MnO2: 10.0-15.5%, C: 5.0-10.5%, and the remainder is the ignition loss component. The remainder is ≤2.0%.
[0030] In some specific embodiments, the basicity of the protective slag is 0.55-0.85, the melting point of the protective slag is 1190-1260° C., and the viscosity of the protective slag is 0.28-0.79 Pa·s.
[0031] In some specific embodiments, the low-basicity protective slag for peritectic alloy steel is made of the following raw materials in parts by weight: 5-8 parts of fluorite, 0-5 parts of wollastonite, 0-3 parts of soda ash, 31-39 parts of manganese slag, 1-11 parts of limestone, 4.5-14 parts of glass powder, 2-5.5 parts of calcined aluminum ash, 4-8 parts of magnesium powder, 10-16 parts of manganese dioxide powder, 3-8 parts of zirconium oxide powder, 2-4 parts of earthy graphite, 2-4 parts of medium carbon graphite, 2-3 parts of carbon black, and 2-3 parts of CMC.
[0032] Among them, manganese slag is the molten waste slag from the bottom of the furnace after smelting metallic manganese, and its chemical composition is as follows by mass percentage: SiO2: 37.0-43.0%, CaO: 20-26.0%, Al2O3: 10.0-16.0%, Fe2O3: 1.0-2.0%, MgO: 4.0-7.0%, MnO2: 10.0-15.0%, and the rest are impurities. A method for preparing the above-mentioned low-basicity protective slag for peritectic alloy steel comprises the following steps: (1) Stir the manganese slag evenly, dry it to make its moisture content ≤1%, and crush it to a particle size of less than 300 mesh and ≥97%; (2) Weighing each raw material by weight, placing it in a pulping tank, adding water and stirring, controlling the slurry concentration to 0.65-0.70%, and preparing a mixed slurry; conveying the mixed slurry to a water mill for grinding, and pumping the ground slurry to the pulping tank during grinding for cyclic grinding; (3) The slurry after circulating grinding is placed in a low-level tank and pressurized into a spray drying tower for spray granulation; (4) Screening out particles with a particle size of 20-80 mesh to obtain the product; (5) Sampling and testing of chemical composition; (6) Packaging and storage.
[0033] In step (2), the stirring time is 10-20 min, and the circulating grinding time is 40-60 min; specifically, the stirring time can be selected from 10 min, 12 min, 15 min, 18 min or 20 min, and the circulating grinding time can be selected from 40 min, 42 min, 45 min, 50 min, 52 min, 55 min or 60 min.
[0034] In step (3), the slurry is pressurized to 1.2-1.8Mpa, the aperture of the spray plate is 2.5mm, the temperature inside the spray drying tower is 450-600°C, the outlet temperature is 150-180°C, and the moisture content of the product is controlled at 0.1-0.35%. Specifically, the slurry pressure can be 1.2Mpa, 1.3Mpa, 1.4Mpa, 1.5Mpa, 1.6Mpa or 1.8Mpa, the temperature inside the spray drying tower can be 450°C, 480°C, 500°C, 520°C, 550°C, 570°C or 600°C, and the outlet temperature can be 150°C, 160°C, 170°C, 173°C or 180°C.
[0035] The following is a specific implementation plan.
[0036] The chemical composition of manganese slag is calculated in mass percentage as follows: SiO2: 40.0%, CaO: 23.0%, Al2O3: 14.0%, Fe2O3: 1.0%, MgO: 6.5%, MnO2: 9.7%, and the rest are impurities.
[0037] The mass percentage of Al2O3 in the calcined aluminum ash is ≥75%.
[0038] Examples 1-8 A method for preparing low-basicity protective slag for peritectic alloy steel comprises the following steps: Stir the manganese slag evenly, dry it to make its moisture content ≤1%, and crush it to a particle size of less than 300 mesh and ≥97%; Weigh each raw material according to the weight parts shown in Table 1, place it in a pulping tank, add water and stir for 15 minutes, control the slurry concentration to 0.68%, and prepare a mixed slurry; transport the mixed slurry to a water mill for grinding, and pump the ground slurry to the pulping tank while grinding, and circulate the grinding for 50 minutes; The slurry after circulating grinding is placed in a low-level tank and pressurized into a spray drying tower. The slurry is pressurized to 1.5Mpa, the aperture of the spray plate is 2.5mm, the temperature inside the spray drying tower is 520℃, the outlet temperature is 165℃, and spray granulation is performed. The moisture content of the product is controlled at 0.2%; The particles with a particle size of 50 mesh were screened out to obtain the product; the chemical composition of the sample was tested as shown in Table 2, which met the requirements; the product was packaged and put into storage.
[0039] Table 1 Raw material composition of low basicity protection slag for peritectic alloy steel (parts by weight) Table 2 Chemical composition of low basicity mold slag for peritectic alloy steel (mass percentage, %) The following are application cases of protective slag in Examples 1-8.
[0040] Case 1: Steel type: peritectic steel LC590, main components of molten steel: C: 0.08-0.095%, Mn: 1.65-1.75%, Si: 0.12-0.23%, Cr: 0.28-0.32%, Mo: 0.13-0.17%; cross section (mm) 230×1500, constant pulling speed: 1.1m / min, casting temperature: 1535℃, casting time for the whole casting is 16h, after the protection slag of Example 1 is added, the spreadability is good, the air permeability is good, the flame is uniform, the liquid slag layer is 11-15mm, and the consumption is 0.41kg / t steel.
[0041] Case 2: Steel type: peritectic steel 12Cr1MoVG, main components of molten steel: C: 0.08-0.014%, Mn: 0.40-0.70%, Si: 0.17-0.37%, Cr: 0.90-1.20%, Mo: 0.25-0.35%, V: 0.15-0.30%; cross section 310×360, constant pulling speed: 0.75m / min, casting temperature: 1542℃, casting time for the whole casting is 8h, after the protection slag of Example 2 is added, the spreadability is good, the air permeability is good, the flame is uniform, the liquid slag layer is 8-12mm, and the consumption is 0.35kg / t steel.
[0042] Case 3: Steel type: peritectic steel 14Mn, main components of molten steel: C: 0.11-0.15%, Mn: 1.05-1.25%, Si: 0.17-0.35%; cross section 165×165, constant pulling speed: 1.6m / min, casting temperature: 1536℃, casting time for the whole casting is 10h, after the protection slag of Example 3 is added, the spreadability is good, the air permeability is good, the flame is uniform, the liquid slag layer is 6-10mm, and the consumption is 0.26kg / t steel.
[0043] Case 4: Steel type: peritectic steel P91 (10Cr9Mo1VNbN), main components of molten steel: C: 0.08-0.12%, Mn: 0.3-0.6%, Si: 0.2-0.5%, P≤0.02, S≤0.01, Cr8.0~9.5, Mo0.85~1.05, V0.18~0.25, Nb0.06~0.1, N0.03~0.07, cross-section 240×240, constant pulling speed: 0.9m / min, casting temperature: 1530℃, casting time for the whole casting is 9h, after the protection slag of Example 4 is added, the spreadability is good, the air permeability is good, the flame is uniform, the liquid slag layer is 8-12mm, and the consumption is 0.33kg / t steel.
[0044] Case 5: Steel type: peritectic steel WL980X, main components of molten steel: C: 0.08-0.10%, Mn: 2.25-2.55%, Si: 0.50-0.60%, Cr: 0.48-0.58%, Ti: 0.015-0.035%, P≤0.003%, S≤0.003%; cross section 220×1650, constant pulling speed: 1.0m / min, casting temperature: 1538℃, casting time for the whole casting is 12h, after the protection slag of Example 5 is added, the spreadability is good, the air permeability is good, the flame is uniform, the liquid slag layer is 10-14mm, and the consumption is 0.45kg / t steel.
[0045] Case 6: Steel type: peritectic steel 12CrMo, main components of molten steel: C: 0.10-0.14%, Mn: 0.60-0.90%, Si: 0.20-0.60%, Cr: 0.40-0.70%, Mo: 0.15-0.25%, P≤0.025%, S≤0.025%; cross section 390×510, constant pulling speed: 0.50m / min, casting temperature: 1545℃, casting time for the whole casting is 9h, after the protection slag of Example 6 is added, the spreadability is good, the air permeability is good, the flame is uniform, the liquid slag layer is 8-12mm, and the consumption is 0.42kg / t steel.
[0046] Case 7: Steel type: peritectic steel 10MnSiTi, main components of molten steel: C: 0.07-0.12%, Mn: 1.40-1.70%, Si: 0.50-0.80%, Ti: 0.06-0.12%, P≤0.03%, S≤0.03%; cross section 300×340, constant pulling speed: 0.75m / min, casting temperature: 1526℃, casting time for the whole casting is 10h, after the protection slag of Example 7 is added, the spreadability is good, the air permeability is good, the flame is uniform, the liquid slag layer is 8-13mm, and the consumption is 030kg / t steel.
[0047] Case 8: Steel type: peritectic steel W1180, main components of molten steel: C: 0.10-0.13%, Mn: 2.40-2.60%, Si: 0.10-0.30%, Als: 0.03-0.05%, Cr: 0.50-0.60%, Nb: 0.02-0.05%, Mo: 0.20-0.30%, Ti: 0.02-0.03%, P≤0.018%, S≤0.003%; cross section 370×2600, constant pulling speed: 0.7m / min, casting temperature: 1533℃, casting time for the whole casting is 16h, after the protection slag of Example 8 is added, the spreadability is good, the air permeability is good, the flame is uniform, the liquid slag layer is 10-14mm, and the consumption is 0.48kg / t steel.
[0048] The following is a comparative test example.
[0049] Comparative Example 1: Different from Example 1, the manganese slag is replaced by equal weight portions of pre-melted base material, and the chemical composition of the pre-melted base material is calculated by weight (mass percentage %): CaO 450 parts (51.1%), SiO 2 350 parts (39.8%), Al 2 O 3 60 parts (6.8%), and MgO 20 parts (2.3%).
[0050] Comparative Example 2: Different from Example 1, the amount of manganese dioxide powder added is 0.
[0051] Comparative Example 3: Different from Example 1, the amount of zirconium oxide powder added is 0.
[0052] Comparative Example 4: Different from Example 1, manganese dioxide powder is replaced by an equal weight portion of manganese carbonate.
[0053] Comparative Example 5: A protective slag is made from the following raw materials in parts by weight: 10 parts of fluorite, 20 parts of wollastonite, 6 parts of soda ash, 28 parts of manganese slag, 7 parts of limestone, 1 part of glass powder, 2 parts of calcined aluminum ash, 4 parts of magnesium powder, 6 parts of manganese dioxide powder, 5 parts of zirconium oxide powder, 2 parts of earthy graphite, 2 parts of medium carbon graphite, 2 parts of carbon black, and 5 parts of CMC.
[0054] The physical and chemical indexes of the protective slag obtained in Examples 1-8 and Comparative Examples 1-5 were tested respectively. The results are shown in Table 3.
[0055] Table 3 Physical and chemical indicators of mold slag The following is an evaluation of the effects of the protective slag of Examples 1-8 and Comparative Examples 1-5.
[0056] The protective slag obtained in Examples 1-8 and Comparative Examples 1-5 was used to prepare peritectic alloy steel 12Cr1MoVG continuous casting billets. The continuous casting process parameters were the same as those in Case 2 and will not be repeated here.
[0057] Observe the spreadability and fluidity of the protective slag during use, and record whether slag ring phenomenon occurs.
[0058] Randomly select each group with a surface area of 1dm 2 For samples, detect and record whether there are obvious cracks, dents, pinholes and other defects on the sample surface; count the microcrack area on the surface of each sample and calculate the microcrack rate. The microcrack rate is the ratio of the microcrack area to the total area of the sample.
[0059] The results are shown in Table 4.
[0060] Table 4 Application effect of protective slag The protective slag prepared by the present invention has good fluidity and spreadability in the crystallizer, and no slag ring phenomenon occurs; there are no obvious cracks and depression defects on the surface of the ingot; the microcrack rate is less than 0.2%. Comparative Examples 1-5 have different degrees of slag rings and crack defects, and the microcrack rate is higher than 2.0%, which is more than 10 times that of the present invention. It can be seen that the protective slag of the present invention has a reasonable composition and ratio, and has good fluidity and spreadability when applied to peritectic alloy steel, without slag rings, and can effectively solve the defects of longitudinal cracks, transverse cracks, microcracks and depressions of peritectic alloy steel, with significant effects.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.
Claims
1. A low-basicity protective slag for peritectic alloy steel, characterized in that: The invention is made of the following raw materials in parts by weight: 5-8 parts of fluorite, 0-5 parts of wollastonite, 0-3 parts of soda ash, 31-39 parts of manganese slag, 1-11 parts of limestone, 4.5-14 parts of glass powder, 2-5.5 parts of calcined aluminum ash, 4-8 parts of magnesium powder, 10-16 parts of manganese dioxide powder, 3-8 parts of zirconium oxide powder, 6-11 parts of carbonaceous material and 2-3 parts of binder.
2. The low-basicity protective slag for peritectic alloy steel according to claim 1, characterized in that: The manganese slag is the molten waste slag from the bottom of the furnace after smelting metallic manganese, and its chemical composition is as follows by mass percentage: SiO2: 37.0-43.0%, CaO: 20-26.0%, Al2O3: 10.0-16.0%, Fe2O3: 1.0-2.0%, MgO: 4.0-7.0%, MnO2: 8.5-12%, and the rest are impurities.
3. The low-basicity protective slag for peritectic alloy steel according to claim 2, characterized in that: The carbonaceous material is a composition of earthy graphite, medium carbon graphite and carbon black, and the mass ratio of the earthy graphite, medium carbon graphite and carbon black is (2-4): (2-4): (2-3).
4. The low-basicity protective slag for peritectic alloy steel according to claim 3, characterized in that: The binder is sodium carboxymethyl cellulose or dextrin.
5. The low-basicity protective slag for peritectic alloy steel according to claim 4, characterized in that: Its chemical composition, in mass percentage, is: SiO2: 18.5-25.5%, CaO: 12.3-22.0%, MgO: 5.5-10.0%, Fe2O3: 0.4-0.5%, Al2O3: 6.0-10.2%, Na2O: 0.75-4.0%, F: 2.3-4.0%, ZrO2: 2.5-8.5%, MnO2: 10.0-15.5%, C: 5.0-10.5%, and the remainder is the loss on ignition component.
6. The low-basicity protective slag for peritectic alloy steel according to claim 5, characterized in that: The basicity of the protective slag is 0.65-0.85, the melting point of the protective slag is 1190-1260° C., and the viscosity of the protective slag is 0.28-0.79 Pa·s.
7. The method for preparing a low-basicity mold slag for peritectic alloy steel according to claim 6, characterized in that: The following steps are involved: (1) Stir the manganese slag evenly, dry it to make its moisture content ≤1%, and crush it to a particle size of less than 300 mesh and ≥97%; (2) Weighing each raw material by weight, placing it in a pulping tank, adding water and stirring, controlling the slurry concentration to 0.65-0.70%, and preparing a mixed slurry; conveying the mixed slurry to a water mill for grinding, and pumping the ground slurry to the pulping tank during grinding for cyclic grinding; (3) The slurry after circulating grinding is placed in a low-level tank and pressurized into a spray drying tower for spray granulation; (4) Screening out particles with a particle size of 20-80 mesh to obtain the product; (5) Sampling and testing of chemical composition; (6) Packaging and storage.
8. The method for preparing a low-basicity mold slag for peritectic alloy steel according to claim 7, characterized in that: In the step (2), the stirring time is 10-20 minutes, and the circulating grinding time is 40-60 minutes.
9. The method for preparing a low-basicity mold slag for peritectic alloy steel according to claim 8, characterized in that: In the step (3), the slurry is pressurized to 1.2-1.8 MPa, the aperture of the spray plate is 2.5 mm, the temperature inside the spray drying tower is 450-600° C., the outlet temperature is 150-180° C., and the moisture content of the product is controlled at 0.1-0.35%.